The complete mitochondrial genome sequence of Taxonus zhangi Wei, 1997 (Hymenoptera: Tenthredinidae) with phylogenetic analysis. Issue 11 (2nd November 2021) - Xu, Min; Tan, Beibei; Wei, Meicai; Niu, Gengyun
Abstract: The complete mitochondrial genome of Taxonus zhangi was 16, 002 bp in size, comprises 13 protein-coding genes (PCGs), two rRNA genes, 22 tRNA genes, and large non-coding A + T region. The phylogenetic result confirms the monophyly of Taxonina and Allantina, and also supports that Xenapateini is the sister group of Allantini which is composed of Taxonina and Allantina.